EFEKTIFITAS TERAPI TUINA CHUZHEN MEDITATIF, AKUPUNTUR DAN FOOD THERAPY TCM TERHADAP INSOMNIA - Agussalim, Wijono Sukaputra; Wardani, Frisca Desma Ayu Kusuma; Ningrum, Niken Kurnia (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2022)
Background : Insomnia is a prevalent sleep problem. A person who consistently has trouble falling asleep or wakes up early has insomnia (Yustinus, 2006). Despite the fact that some of these pharmaceutical treatments are generally accessible, their long-term clinical use is constrained by serious side effects include addiction, allergic responses, vertigo, and gastrointestinal disturbances. In order to lessen the adverse effects of prescription medications, non-pharmacological therapeutic methods for insomnia are required. Objective: The effectiveness of TCM dietary treatment, acupuncture, and meditative Tuina Chuzhen therapy against sleeplessness Method : The technique that involves giving patients or subjects direct instruction or demonstration result : The calming effects of back massage enhance blood flow to the tissues, lessen the burden on the heart, stimulate blood flow to deeper blood vessels, speed up metabolic and nutritional processes, and lessen anxiety and sadness. Keywords : Traditional Chinese Medicine, tuina chuzhen, and sleeplessness